Atezolizumab in a CoHort of pretreated, advanced, non-small cell lung cancer patients with rare HistologiCal SubtypEs (CHANCE trial). (July 2020) - Gelsomino, Francesco; Lamberti, Giuseppe; Tiseo, Marcello; Rocco, Danilo; Pasello, Giulia; Cecere, Fabiana Letizia; Chella, Antonio; Grilli, Giada; Mandruzzato, Marcella; Tognetto, Michele; Garassino, Marina Chiara; Macerelli, Marianna; et al.
Background: Although immunotherapy with immune-checkpoint inhibitors (ICIs) has profoundly changed the therapeutic scenario in the treatment of advanced non-small cell lung cancer (NSCLC), trials of ICIs only enrolled NSCLC patients with common histology. Atezolizumab was approved by the United States Food and Drug Administration (US FDA) in October 2016 and by the European Medicines Agency (EMA) in September 2017 for the treatment of patients with metastatic NSCLC whose disease progressed during or following platinum-containing chemotherapy, regardless of PD-L1 expression. Methods: We designed a single-arm, multicenter, two-stage phase II study and plan to enroll 43 patients. The primary objective of the study is to evaluate the antitumor activity of atezolizumab in advanced NSCLC patients with rare histology subtypes. Patients with prior atezolizumab or ICI treatment and with untreated, symptomatic, or progressing brain metastases will be excluded. The primary endpoint is disease control rate. Secondary objectives are toxicity and safety, overall response rate, progression-free survival, overall survival, and time to progression. Diagnosis of NSCLC with rare histology will be confirmed by central pathology revision, and will include: colloid carcinoma, fetal adenocarcinoma, non-endocrine large cell carcinoma, sarcomatoid carcinoma, salivary gland-type tumor, lymphoepithelioma-like carcinoma, and NUT-nuclear protein in testis carcinoma. Archival tumor tissue is required for correlative studies of PD-L1 expression on tumor cells and tumor infiltrating lymphocytes. Conclusions: Therapeutic options in NSCLC with rare histology subtypes, to be assessed in specifically designed trials, are an unmet need. This trial will help elucidate the role of atezolizumab as a viable option in this setting.